1990
DOI: 10.1017/s0043174500056599
|View full text |Cite
|
Sign up to set email alerts
|

Self-Limitation of Herbicide Mobility by Phytotoxic Action

Abstract: Translocation of phloem-mobile herbicides was inhibited by their phytotoxic action on processes that maintain assimilate translocation. Glyphosate lowered import into developing sink leaves soon after it was applied to exporting sugarbeet leaves. Later, photosynthesis slowed down and starch accumulation stopped, but export of both assimilate and glyphosate continued until it was limited by starch availability at night Experiments with field pennycress and Tartary buckwheat indicated that self-limitation of chl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
0
1

Year Published

1992
1992
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 24 publications
8
56
0
1
Order By: Relevance
“…These results appear to support evidence suggesting that glyphosate interferes with the plant processes which maintain phloem transport 6, 19–22. In sugarbeet, a decline in photosynthesis is followed by slowing down of import into sink leaves, apparently reflecting interference with metabolism in the developing leaves 6. This was attributed to a decrease in photosynthesis, resulting in a corresponding decrease in the rate of sucrose synthesis and translocation.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results appear to support evidence suggesting that glyphosate interferes with the plant processes which maintain phloem transport 6, 19–22. In sugarbeet, a decline in photosynthesis is followed by slowing down of import into sink leaves, apparently reflecting interference with metabolism in the developing leaves 6. This was attributed to a decrease in photosynthesis, resulting in a corresponding decrease in the rate of sucrose synthesis and translocation.…”
Section: Discussionsupporting
confidence: 81%
“…Phloem movement of glyphosate is presumably controlled by factors which influence assimilate translocation. This is illustrated by the work of Geiger and Bestman6 using sugarbeet leaves. They found that lowering of photosynthesis and starch accumulation on the first day appeared to diminish the duration of glyphosate transport on subsequent days by depriving the plant of some stored carbohydrate that could prolong phloem transport from the treated source leaves.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sensitive and responsive control is needed to regulate the PCR cycle because its metabolite pools are quite small compared to the flux through them (Geiger and Bestman, 1990). A small imbalance between the rate at which a given metabolite is produced and that at which it is used causes a large excursion in the level of the metabolite.…”
Section: Dynamic Regulation Of the Pcr Cycle In Response To Lightmentioning
confidence: 99%
“…Although glyphosate can result in inhibition of its own translocation to sink tissues (Geiger and Bestman 1990), high rates (e.g., 2.2 kg/ha) have been shown to be as effective against annual weeds as lower recommended rates (Smith et al 1998). Further research should be conducted to determine if multiple applications of glyphosate at rates higher than those recommended for annual weeds used for multiple years significantly reduce redvine populations to a level comparable with expensive preharvest herbicide treatments (e.g., dicamba).…”
Section: Resultsmentioning
confidence: 99%